Psychology of Learning - "Deese, James" (NewYork, 1958)
Learning occupies one of the central positions in psychology, and an understanding of the psychology of learning should be useful to almost every serious student of psychology. The aim of this book is bring together for the student the divergent interest in the psychology of learning. The book is principally addressed to the junior or senior student in psychology, graduate student in psychology and in educational psychology will find it useful.
Keywords: Psychology